Soil microbial community succession and physicochemical property changes affect Ganoderma leucocontextum growth in the Dadu river basin - Zhang, Bo; Yang, Xuezhen; Tian, Qing; Ye, Lei; Huang, Zhenzhu; Tan, Wei; Zhou, Lei; Chen, Hang; Li, Xiaolin (Frontiers in Microbiology, 2026)
Ganoderma leucocontextum is rich in bioactive compounds, including triterpenes and polysaccharides, and exhibits significant pharmacological effects. Its cultivation requires casing soil, crucial for achieving high productivity and superior quality. In this study, soil physicochemical properties and microbial communities were analyzed across four growth stages: casing (GCK), primordial (G1p), cap (G1c), and maturity (G1m) of G. leucocontextum. Results indicated that the soil pH significantly increased after cultivation, ranging from 6.78 to 7.11. The control soil contained the highest concentrations of total nitrogen (2.44 g/kg), available nitrogen (259.48 mg/kg) and organic matter (54.35 g/kg), significantly exceeding those in G. leucocontextum-cultivated soils. Soil available phosphorus and potassium gradually increased, peaking at maturity (42.01 mg/kg and 86.36 mg/kg, respectively). Microbial communities also shifted from bacterial to fungal dominance over time. Among bacteria, Acidobacteriota was the most prevalent phylum, averaging 28.46%, with a marked upward trend. Arthrobacter emerged as the most dominant genus, averaging 9.00%, with higher abundance at maturity. A Vicinamibacterales-order genus continuously increased in abundance, wheras Novocardioides, Sphingomonas, and an Intrasporangiaceae-family genus decreased during of G. leucocontextum growth. For fungi, Ascomycota was the most prevalent phylum, averaging 65.56%, followed by Basidiomycota at 21.60%, which dominated at maturity. Ganoderma was the most predominant genus, averaging 16.34%, and increased substantially with growth. The study revealed correlations between soil microbial communities and physicochemical properties, and demonstrated decreasing polysaccharide content but increasing triterpenoid acid content during growth. This research explores soil microbial community succession and physicochemical changes for G. leucocontextum cultivation, offering theoretical support for overcoming continuous cropping obstacles (CCOs) and insights for sustainable yield management.